An In-Depth Analysis of Cancer Trends and Implication from Champhai District of Mizoram, Northeastern India - Beihrosa Solo; Lalhmangaihzuali Ralte; Lalramliana, C (The Bioscan, 2024)
A retrospective study was conducted to analyze the prevalence and distribution of cancer types in 807 patients from Champhai District, Mizoram, northeastern India, during the period 2015–2020. The study identified 30 distinct types of cancer, with stomach cancer being the most common, accounting for 20.20% (163 cases), followed by lung cancer at 15.61%. Breast cancer emerged as the third most prevalent cancer, contributing 8.55% (69 cases) and was notably common among the female population. Moderately occurring cancers included bone cancer (3.22%), colon cancer (3.35%), gall bladder cancer (3.59%), mouth cancer (3.84%), and rectum cancer (3.59%). Cancers of lower occurrence included brain cancer, thyroid cancer, ovary cancer, skin cancer, and prostate cancer. Rare cancer types identified included anus/anal cancer (0.12%), eye cancer (0.25%), kidney cancer (0.74%), larynx cancer (0.74%), leukemia (0.12%), tongue cancer (0.62%), throat cancer (0.37%), tonsil cancer (0.37%), mesenteric cancer (0.12%), penile cancer (0.99%), and urinary bladder cancer (0.25%). These findings highlight the diversity in cancer prevalence within the study area, emphasizing the need for region-specific cancer prevention and management strategies.